Moving Gyeongseong: Korean Reaction to Changes in the Urban Landscape of Colonial Seoul in the 1920s. - Song, Jane Ga-Young. (Tufts Archival Research Center, 2005)
The 1920s building boom in Gyeongseong (the name of Seoul during the Japanese occupation of 1910-1945) created a modern geography that had not existed before. Korean residents traveled along the widened roads that connected all the major city monuments, absorbed their new environment sculpted by imposing western-style buildings, and congregated in public places ("officially sanctioned social places") that were supposed to turn them into dutiful colonial subjects. Modernization of Gyeongseong's physical space was an integral part of the colonial discourse; the colonial government hoped that the burgeoning modernity of the colony would gain Koreans' compliance, or at least passive acceptance, of the colonial order. My research found that Gyeongseong's immediate physical spaces "landmarks symbolizing colonial power, parks, and downtown commercial streets" entertained, impressed, and attracted urban Koreans, but they also revealed the extent of cultural, political, and economic discrimination that Koreans faced in a city that no longer belonged to them. I will argue that this ambiguous, uneven, and contradicting response from the everyday physical space of Korean colonial modernism was a critical one; the dissenting voices contributed to the pervading nationalistic mood of the time period. The 1920s is generally seen as Japan's most "successful" period of colonization, for its modernizing efforts and more lax policies led to the "most effective form of manipulation" in Korea. Nevertheless, in hindsight it is evident that the 1920s had many contradictions and largely failed to produce "model colonial subjects" even in Gyeongseong's small middle class who welcomed modernity in Korea.